2018
DOI: 10.1177/0363546518758950
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an MRI Protocol for Routine Quantitative Assessment of Tunnel Position in Anterior Cruciate Ligament Reconstruction

Abstract: This study demonstrated that, in addition to being the optimum modality for assessment of soft tissue injury of the knee, a high-resolution 3D turbo spin echo proton density sequence can provide an accurate assessment of tunnel placement, without the use of ionizing radiation. Therefore, this protocol provides the foundation for an objective standardized platform to quantitatively evaluate the location of ACL bone tunnels and graft orientation for routine postoperative assessment, presurgical planning, and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
14
1
1
Order By: Relevance
“…This protocol included volumetric and near isotropic (0.5 3 0.5 3 0.65 mm) turbo spin echo sequences, which allowed multiplanar reconstructions along the ACLR and subsequent accurate anatomic measurements previously validated against 3-dimensional computed tomography. 13 Femoral notch volume, graft measurement and orientation, tunnel locations, and graft SI were recorded.…”
Section: Mri Measurementmentioning
confidence: 99%
“…This protocol included volumetric and near isotropic (0.5 3 0.5 3 0.65 mm) turbo spin echo sequences, which allowed multiplanar reconstructions along the ACLR and subsequent accurate anatomic measurements previously validated against 3-dimensional computed tomography. 13 Femoral notch volume, graft measurement and orientation, tunnel locations, and graft SI were recorded.…”
Section: Mri Measurementmentioning
confidence: 99%
“… 13 , 24 , 25 Grasso et al. 26 proposed an MRI protocol for routine quantitative assessment of tunnel position in ACL reconstruction, but MRI is not easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…20,40,49 MRI undoubtedly has a role in planning revision surgery for 10 found that angle measurements did not differ between CT and MRI and suggested that MRI can be used to replace CT for identifying tunnel placement. Grasso et al 14 performed grid measurements on CT and MRI; however, the measurements were conducted on computer-generated models after adding digitized information acquired during revision surgery, not on actual CT or MRI scans. In our view, the clinical usefulness of angle and grid measurements on MRI has not been sufficiently established to date.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that there is little difference between angle measurements performed on MRI and CT and grid measurements performed on CT and 3D-MRI. 10,14 However, it is not known if both methods are equally adept in identifying the nonanatomic placement of grafts.…”
mentioning
confidence: 99%